Analysis of the Millennial Generation's Perspective Becoming Young Entrepreneurs during the Covid-19 Pandemic - Nawangsih Nawangsih; Hassan Touati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Previous research related to millennials who are interested in becoming young entrepreneurs, can be an interesting study, especially during the covid 19 pandemic. The research objectives are: 1. To find out the millennial generation's perspective on young entrepreneurs, 2. To identify the factors that influence the millennial generation to be young entrepreneurs and 3. To find out the form of productive economic business opportunities created by the millennial generations. This research is a qualitative type using a literature study approach. Scientific reference sources are taken from various sources that are relevant to the theme of the research carried out as well as from various reference books as a reference for the theory taken. The results showed that the millennial generation's perspective on young entrepreneurs during the current covid 19 pandemic, responded very positively, where the millennial generation who updated digital technology, and made technology a part of their lives, felt they had a greater opportunity to become a young entrepreneur.